X-ray and proton measurements from petawatt laser interactions - Patel, P; Mackinnon, A; Heathcote, R; Foord, M; Gregori, G; Key, M; King, J; Moon, S; Park, H; Pasley, J; Theobald, W; Town, R; et al. (Optical Society of America, 2006)
We describe measurements characterizing the interaction of ultra-high intensity Petawatt laser pulses with solid targets. Experiments were performed on the Petawatt laser at RAL, and the Titan laser at LLNL. © 2006 Optical Society of America.